Awareness and handling of the dangers of Electronic waste (survey study) (Libya Journal of Geographical Studies, 2023)
Waste electrical and electronic equipment is a rapidly growing problem worldwide and can cause environmental and health problems due to its content of hazardous materials such as heavy metals and others. On the other hand, awareness and recycling of e-waste is an important issue to ensure the successful management, classification and sorting of e-waste according to international standards.This study provides information on the knowledge, awareness and behavior of university students in dealing with, disposal, recycling and management of waste electrical and electronic equipment, as measured through a field survey in the form of an electronic questionnaire for students of the Faculty of Public Health (University of Benghazi) from the three departments: Nutrition, Environmental Health and Health Services Administration For the third and fourth years in the first months of 2022, a regular random sample of 250 students was selected from a total of 568 students. The main results of the study indicate that 60% of the sample is familiar with the concept of electrical and electronic waste. Most of the participants believe that e-waste has health and environmental risks (80.8%), and most participants would like to recycle e-waste (81.2%) and participate in the recycling program provided that the authorities establish awareness programs about the importance of treatment and recycling (53.6%) of this waste. In addition to setting up a comprehensive mechanism for collecting and sorting e-waste and then transferring it to a body designated to deal with it, imposing fines for dumping e-waste in streets and public squares, and creating awareness through workshops and media awareness about the dangers of e-waste and how to treat it.
Keywords: E-waste; awareness; risk; management; knowledge